Review of materials characterization techniques to study corrosion in biodiesel engines - Corrales-Brenes, Rebeca (2022)
Biodiesel is a biodegradable alternative that makes it possible to replace part of the consumption of petroleum diesel. This article analyzes the corrosive effect of biodiesel on metallic materials in engines using characterization techniques, including Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, scanning electron microscopy (SEM) and X-ray diffraction (XRD). Through a study of the state of the art of these techniques, recommendations are gathered to evaluate the performance of metals in engines that run on biodiesel. In addition, it covers the corrosion mechanisms to which engine components are subjected to improve their design processes. The study finally focuses on pitting corrosion to identify viable strategies to mitigate its effect on this type of engines and improve their performance characteristics, for which materials science is demonstrated as a fundamental tool. The main result of this review was the identification of pitting corrosion as the main failure mechanism in biodiesel engines.